The relationship between the use of combined hormonal contraception with a predominance of gestagens and the selected types of female body in young women from the region of Lower Silesia - Karykowska Aleksandra; Kwiatkowska Barbara; Grzelak Joanna; Kurc-Darak Bożena; Domagała Zygmunt (Anthropological Review, 2018)
Oral contraceptive agents are currently the most popular and one of the most effective methods for preventing pregnancy. The data shows that over 300 million women in the world use contraceptive drugs containing synthetic hormones to avoid an unwanted pregnancy. Their effects may affect other systems, leading to the occurrence of various problems associated with the use of the drug. The aim of the study is to estimate the frequency of prevalence of subjective effects associated with the use of combined hormonal contraception with a predominance of gestagens by young women Surveys were conducted among female students of Wrocław universities from December 2010 to January 2011. They covered 257 women aged statistically 23.58 (SD=2.95). They were divided into three age classes: 19-22, 23-24, 25-28. The individual age of menarche and the hormonal type of body were determined. Only persons with a gestagenic or estrogenic type of body were qualified for the study. Results: 64.6% of all respondents declared the use of hormonal contraception. Combined agents with a predominance of gestagens constituted 87% in this group. Their use brings both positive (90%) and negative (65%) aspects. The most common positive effects include high contraceptive effectiveness, regulation of menstruation and minimisation of skin problems. The most frequent negative effects include: weight gain, spotting, breast swelling and decreased libido. Surprisingly, the study did not show any correlation between the hormonal type and the occurrence of side effects. There was no significant statistical relationship between the type of hormonal contraception used and the hormonal type.